Back Cover: Enhanced Thermal Oxidation Stability of Reduced Graphene Oxide by Nitrogen Doping (Chem. Eur. J. 38/2014). Issue 38 (15th September 2014) - Sandoval, Stefania; Kumar, Nitesh; Sundaresan, A.; Rao, C. N. R.; Fuertes, Amparo; Tobias, Gerard
<x xml:space="preserve">Abstract</x> The presence of nitrogen heteroatoms within the lattice of reduced graphene oxide sheets induces a remarkable increase in the thermal stability against oxidation by air. This phenomenon is represented by a nitrogen‐doped (blue spheres) graphene sheet withstanding a flame. For more details, see the Communication by C. N. R. Rao, G. Tobias et al. on page 11999 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>